Methods of primary clinical prevention of dental caries in the adult patient: an integrative review - Veiga, Nélio (2023)
Aim: Preventive approaches to oral health diseases, mainly dental caries, require individual and collective policies. Thus, this review was conducted to identify the primary prevention methods of dental caries in adults to improve oral health at the clinical and community levels. Methods: This review followed the PICO strategy with the research question: “What are the methods of primary prevention of dental caries, in adults, for improving and maintaining oral health integrating clinical and community-based strategies?” Electronic screening was carried out by two independent reviewers in five databases (MedLine/PubMed, SciELO, Web of Science, Cochrane Library, and LILACS) to find relevant publications between 2015–2022. We applied eligibility criteria for selection of the articles. The following MeSH terms were used: “Primary Prevention”; “Adult”; “Oral Health”; “Dental Caries”; “Fluorides, Topical”; “Fluoride Varnishes”; “Pit and Fissure Sealants”; “Preventive Dentistry”. Although the term “Prevention strategy” is not a MeSH descriptor, several correlated terms appeared and were used in the search engines: “Preventative Care”, “Disease Prevention, Primary”, and “Prevention, Primary”. The tool provided by the JBI organization (Joanna Briggs Institute) was used to assess the quality of the included studies. Results: Nine studies were included. Overall, it was found that the main primary prevention methods applied in dentistry in adults are the application of pit and fissure sealants, topical application of fluoride performed in the dental clinic, use of fluoridated toothpaste, mouthwash with chlorhexidine at home, use of xylitol, the recommendation for regular appointments with the dentist, and the need to inform patients about the saliva buffer capacity and adoption of a non-cariogenic diet. For that purpose, preventive policies should be taken to prevent dental caries. These include three major challenges: providing the adult population with more knowledge regarding their oral health, empowering patients through adopting healthy lifestyles, and developing new preventive strategies and awareness campaigns aimed at the adult population to promote proper oral health habits. Conclusions: A small number of studies were found whose participants were adult patients. There was some consistency regarding primary prevention methods in our studies. However, good quality randomized control studies are still required to define the best intervention strategies for adult caries prevention.